(N|KSPERIMENTALXNYE ISSLEDOWANIQ ATMOSFERNOJ DIFFUZII I RAS^ETY RASSEQNIQ PRIMESI (B/s - (NbYZOWA(B, (NnATALXQ lEONTXEWNAs; (NgARGER(B, (NeWGENIJ kONSTANTINOWI^s; (NiWANOW(B, (NwLADISLAW nIKOLAEWI^s ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 258-272 (316 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 273-276s
Keywords: (NaTMOSFERAs -- (NzAGRQZNENIEs; (NtURBULENTNOSTXs